City of Baraboo 2007 river corridor redevelopment survey report - Hadley, Shelly; Trechter, David; Parks, Denise; Janke, James (My University, 2007)
The City of Baraboo River Corridor Redevelopment Survey was designed to gather baseline information that would help the City of Baraboo assess the impact of the river corridor redevelopment project funded by the Wisconsin Department of Commerce. It is anticipated that a follow-up survey will be conducted in approximately five years.
37 p.
Keywords: Baraboo, Wisconsin; Baraboo (Wis.); Baraboo River (Wis.); Baraboo River Corridor (Wis.)--Planning; Baraboo River Corridor redevelopment project; Waterfronts--Wisconsin--Baraboo--Planning; Central business districts--Wisconsin--Baraboo--Planning; City planning--Wisconsin--Baraboo